Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1001/jamasurg.2014.1338
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients With Postoperative Complications Who Are at Risk for Failure to Rescue

Abstract: Twenty percent of high-risk patients account for 90% of failure to rescue (Pareto principle). More than two-thirds of patients with failure to rescue have multiple complications. On average, a few days elapse before death following a complication. A risk-scoring system based on preoperative variables predicts patients in the highest-risk category of failure to rescue with good accuracy. In high-risk patients who develop complications, our results suggest that early intervention, preferably in a high-level inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 38 publications
2
48
1
3
Order By: Relevance
“…The term 'failure to rescue' attempts to take into account that it is not the occurrence of complications per se but rather the handling of these that is important. It also describes the disease-specific mortality after operative interventions as an important hospital quality parameter [45][46][47][48]. The use of trained personnel and specialization in intensive care units are also crucial [49].…”
Section: 'Failure To Rescue': the Handling Of Complications Is Importantmentioning
confidence: 99%
“…The term 'failure to rescue' attempts to take into account that it is not the occurrence of complications per se but rather the handling of these that is important. It also describes the disease-specific mortality after operative interventions as an important hospital quality parameter [45][46][47][48]. The use of trained personnel and specialization in intensive care units are also crucial [49].…”
Section: 'Failure To Rescue': the Handling Of Complications Is Importantmentioning
confidence: 99%
“…Surgeries, of course, come with a host of risks, including death. 3 In addition to the expected risks such as bleeding, infection and anesthetic problems, gynaecological surgeries pose a set of unique risks. Due to the close proximity of the female genital organs to the bowel and urinary tract, gynecological surgeries present risks for intra-operative injury to the ureters, bladder and bowel as well as the major pelvic blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…43 In addition, they showed that cardiac events, pulmonary failure, renal failure, and stroke tended to have much higher failure-to-rescue rates, most of which occurred one week before post-operative mortality. 43 These findings are consistent with our data, suggesting that a frequent observation and timely intervention can potentially reduce failure to rescue during the limited period for rescue. A variety of factors are known to decrease the failure-to-rescue rate, such as aggressive and extreme interventions, and high-quality structural components, including better ICU care, nurse to patient ratios, involvement of residents and subspecialty surgeons, and effective teamwork.…”
Section: Articlementioning
confidence: 99%
“…Ferraris et al (2014) discussed the importance of identifying the minority of patients who were likely to die so that more intensive postoperative care can be provided for them to reduce the failure-to-rescue rate. 43 In addition, they showed that cardiac events, pulmonary failure, renal failure, and stroke tended to have much higher failure-to-rescue rates, most of which occurred one week before post-operative mortality. 43 These findings are consistent with our data, suggesting that a frequent observation and timely intervention can potentially reduce failure to rescue during the limited period for rescue.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation